The Effect of Prognostıc Factors and Potentıal Treatment Regımens on Fatality Covid-19 Patıents - Ahmet Doğan; Hatun Öztürk Çerik; Atila Gürgen; Aykut Özturan (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2020)
The ongoing outbreak of the coronavirus disease 2019 (COVID-19), as named by the World Health Organization, has millions of confirmed cases worldwide and has claimed hundreds of thousands of lives. The virus was named SARS-CoV-2 in February by the International Committee on Taxonomy of Viruses. COVID-19 presents as fever, dry cough, dyspnea, headache, and pneumonia. In a small subset of severe cases, the disease quickly progresses to respiratory failure and even death. This study aimed to know the effects of clinical and laboratory features on investigated death. The diagnosis was based on typical findings in thoracic computed tomography (CT) and positive results of the Real-Time Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) SARS-CoV-2. The demographic characteristics of COVID-19 patients treated, accompanying comorbid conditions and laboratory criteria (blood lymphocyte counts, C Reactive Protein (CRP), D-dimer, Interleukin 6 (IL-6), blood neutrophil count/lymphocyte counts) were collected retrospectively. The results show that 121 cases, 66 (54.54%) were male, 55 (45.46%) were female, and the mean age was ± Std (Min-Max), 59.63 ± 17.4 (22-91). Neutrophil percentage (p = 0.027), neutrophil / lymphocyte ratio (NE / LE) (p = 0.028), CRP (p = <0.001), PCT (p = 0.004), D dimer (p = 0.021) and IL 6 (p = 0.047) in patients with a fatal course, higher values were found than those recovered. Blood lymphocyte count (p = 0.001) and percent (p <0.001) were lower. Number of blood white spheres (p = 0.010), blood neutrophil counts (p = 0.001) and percentage (p <0.001), NE / LE (p0.001), CRP (p <0.001), PCT (p = 0.003) and IL -6 (p <0.001) levels were higher in patients with severe clinical findings than in mild cases. The case death rate was observed as 9%. Covid-19 patients should consider blood neutrophil percentage, blood lymphocyte count, blood lymphocyte percentage, NE / LE, CRP, D dimer, and IL 6 values as an early warning in terms of prognosis. More experience was needed to assess the benefits of immune plasma, tocilizumab, IVIG treatments, and remdesivir therapy recently introduced to the treatment protocol.